Biocrust Amendments to Topsoils Facilitate Biocrust Restoration in a Post-mining Arid Environment - Schultz, Nick L.; Sluiter, Ian R. K.; Allen, Geoffrey G.; Machado-de-Lima, Nathali M.; Muñoz-Rojas, Miriam (Frontiers in Microbiology, 2022)
Soil cryptogamic biocrusts provide many ecological functions in arid zone ecosystems, though their natural reestablishment in disturbed areas is slow. Accelerating reestablishment of biocrusts may facilitate the establishment of vascular plant communities within the timeframes of restoration targets (typically 5–15 years). One technique is to inoculate the soil surface using slurries of biocrust material harvested from another site. However, this is destructive to donor sites, and hence the potential to dilute slurries will govern the feasibility of this practice at large spatial scales. We conducted a replicated experiment on a disturbed mine site to test the individual and combined effects of two strategies for accelerating soil cryptogamic biocrust reestablishment: (1) slurry inoculation using biocrust material harvested from native vegetation; and (2) the use of psyllium husk powder as a source of mucilage to bind the soil surface, and to potentially provide a more cohesive substrate for biocrust development. The experiment comprised 90 experimental plots across six treatments, including different dilutions of the biocrust slurries and treatments with and without psyllium. Over 20 months, the reestablishing crust was dominated by cyanobacteria (including Tolypothrix distorta and Oculatella atacamensis), and these established more rapidly in the inoculated treatments than in the control treatments. The inoculated treatments also maintained this cover of cyanobacteria better through prolonged adverse conditions. The dilute biocrust slurry, at 1:100 of the biocrust in the remnant vegetation, performed as well as the 1:10 slurry, suggesting that strong dilution of biocrust slurry may improve the feasibility of using this technique at larger spatial scales. Psyllium husk powder did not improve biocrust development but helped to maintain a soil physical crust through hot, dry, and windy conditions, and so the potential longer-term advantages of psyllium need to be tested.